PKM WORKSHOP PEMBUATAN ARTIKEL ILMIAH PADA MAHASISWA PRODI PENDIDIKAN KEPELATIHAN OLAHRAGA IKIP PGRI KALIMANTAN TIMUR - Muhamad Rohadi; Achmad Maulana; Noredyo Molyaningrum; Muhamad Abdurrochim; Hesti Hasanah; Rina Indarti (COVIT (Community Service of Health), 2022)
Scientific writing is writing that is made based on the results of research both from the results of field research and research from the results of library studies which are required for every student who is studying at higher education levels starting from D3 which is referred to as the final project, S1 which is referred to as thesis, S2 is called a thesis and for the S3 level it is called a dissertation. The final results of a research are expected to be able to contribute ideas and innovations in accordance with the field of science being researched/studied. Besides that, research results should not only stop being kept in the library at tertiary institutions, but must be disseminated to the general public as well as a form of effort to enrich one's repertoire/insight in society for a field study as well as a form of science and technology development in that field. The results of PkM activities in outline include the following components: 1. Achievement of training objectives. 2. The ability of participants in mastering the material. 3. The success of the target number of training participants. The target objective of the training in planning is that participants are able to compile scientific research proposals, at a minimum, ideas, titles and research backgrounds. Keywords: Scientific papers